2016
DOI: 10.1016/j.yexcr.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear respiratory factor-1 and bioenergetics in tamoxifen-resistant breast cancer cells

Abstract: Acquired tamoxifen (TAM) resistance is a significant clinical problem in treating patients with estrogen receptor α (ERα) + breast cancer. We reported that ERα increases nuclear respiratory factor-1 (NRF-1), which regulates nuclear-encoded mitochondrial gene transcription, in MCF-7 breast cancer cells and NRF-1 knockdown stimulates apoptosis. Whether NRF-1 and target gene expression is altered in endocrine resistant breast cancer cells is unknown. We measured NRF-1and metabolic features in a cell model of prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…Our findings show that the expression level of BAX/BCL2 was significantly increased in NRF1 silenced LGCs. This is consistent with a previous study, which found that NRF1 silence stimulated MCF-7 breast cancer cell apoptosis (Radde et al 2016). Consequently, the change in mRNA ratio of BAX/BCL2 could destabilize mitochondria, lead to CYCS release from mitochondria to cytoplasm and induce caspases activation (Raisova et al 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings show that the expression level of BAX/BCL2 was significantly increased in NRF1 silenced LGCs. This is consistent with a previous study, which found that NRF1 silence stimulated MCF-7 breast cancer cell apoptosis (Radde et al 2016). Consequently, the change in mRNA ratio of BAX/BCL2 could destabilize mitochondria, lead to CYCS release from mitochondria to cytoplasm and induce caspases activation (Raisova et al 2001).…”
Section: Discussionsupporting
confidence: 91%
“…This was evidenced by, 1) activation of ERK resulted in transcriptional activation of the -272/-191 fragment of the CD47 promoter; 2) this fragment is enriched of consensus binding sites for NRF-1; 3) NRF-1 binds to this fragment that was enhanced by BRAF/MEK inhibitors; 4) knockdown of NRF-1 abolished ERK-mediated upregulation of CD47; In addition, the role of NRF-1 in ERK-mediated CD47 upregulation is supported by the finding that ERK signalling promotes NRF-1 expression. The physiological role of NRF-1 is regulation of transcription of nuclear-encoded mitochondrial genes and thus mediates the biogenomic coordination between nuclear and mitochondrial genomes [ 44 , 45 ]. Its activation involves phosphorylation and relocation from the cytoplasm to the nucleus [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting glycolysis via hexokinase II inhibition decreased Akt/mTOR/HIF-1α signaling and restored Tamoxifen sensitivity in antiestrogen-resistant breast cancer cells [237]. A study corroborating an increase in glycolysis in TAM-R cells also observed a counter intuitive increase in NRF-1 and its target TFAM [238]. Similarly, RNA sequencing studies to identify genes differentially expressed in tamoxifen-resistant vs. -sensitive cells found gene expression pattern suggesting dysfunctional mitochondria and altered OXPHOS in TAM-R cells [239].…”
Section: Effects Of Treatment and Resistance To Soc On Metabolic Rmentioning
confidence: 99%